Reverse Marketing and its Effect on Customer Behavior: An Analytical Study of The Opinions of a Sample of Water Subscribers in The Water Directorate of Sulaymaniyah Governorate - شريف, شلير عبدالله; محمد, جلال عبدالله (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The current study aims to reveal the relationship and the effect between demarketing with its dimensions (limited product, high prices, limited distribution, counter advertising) and consumer behavior based on the (AIDA) model of consumer behavior.The study problem includes a set of intellectual and practical questions, and the main question of the study is: Is there a correlation and impact of reverse marketing on consumer behavior? The study attempts to answer the main question and the sub-questions by relying on the descriptive-analytical approach based on a set of scientific and academic sources.To prove the hypotheses of the study from a scientific point of view, a questionnaire was used, consisting of (40) items, and distributed to the residents of the city of Sulaymaniya distributed to a random sample consisting of 15 houses in the (19) areas represented by the study community and consisting of (173942) participants In the Directorate of Water of Sulaymaniya Governorate, the number of distributed forms was (500) and (326) of them were returned, and (285) were valid for analysis and (41) were excluded for damage or were not suitable for analysis, and after distribution the statistical packages program for social sciences was used. (Spss-25), to clarify how to determine the nature of the relationship and the effect between the study variables. The Conclusion It was found that there is a positive correlation between the two variables of the study, which in turn indicates that whenever the requirements of reverse marketing improve in the concerned institution, this contributes to improving consumer behavior levels.The recommendations that the success of the Water Corporation is directly and indirectly affected by its fulfillment of the requirements of reverse marketing in order to be able to direct consumer behavior in accordance with its objectives in rationalizing water use.